Metabolic Syndrome in Italian Obese Children and Adolescents: Stronger Association with Central Fat Depot than with Insulin Sensitivity and Birth Weight - Claudia Brufani; Danilo Fintini; Ugo Giordano; Alberto Enrico Tozzi; Fabrizio Barbetti; Marco Cappa (International Journal of Hypertension)
Aim. To evaluate whether body fat distribution, birth weight, and family history for diabetes (FHD) were associated with metabolic syndrome (MetS) in children and adolescents. Methods. A total of 439 Italian obese children and adolescents (5–18 years) were enrolled. Subjects were divided into 2 groups: prepubertal and pubertal. MetS was diagnosed according to the adapted National Cholesterol Education Program criteria. Birth weight percentile, central obesity index (measured by dual-energy X-ray absorptiometry), insulin sensitivity (ISI), and disposition index were evaluated. Multivariate logistic regression models were used to determine variables associated with MetS. Results. The prevalence of MetS was 17%, with higher percentage in adolescents than in children (21 versus 12%). In the overall population, central obesity index was a stronger predictor of MetS than insulin sensitivity and low birth weight. When the two groups were considered, central fat depot remained the strongest predictor of MetS, with ISI similarly influencing the probability of MetS in the two groups and birth weight being negatively associated to MetS only in pubertal individuals. Neither FHD nor degree of fatness was a significant predictor of MetS. Conclusion. Simple clinical parameters like increased abdominal adiposity and low birth weight could be useful tools to identify European obese adolescents at risk for metabolic complications.